Study of the ℤ3 symmetry in QCD at finite temperature and chemical potential using a worm algorithm - Krein, Gastão [UNESP]; Leme, Rafael R. [UNESP]; Woitek, Marcio [UNESP] (AIP Publishing, 2013)
Traditional Monte Carlo simulations of QCD in the presence of a baryon chemical potential are plagued by the complex phase problem and new numerical approaches are necessary for studying the phase diagram of the theory. In this work we consider a ℤ3 Polyakov loop model for the deconfining phase transition in QCD and discuss how a flux representation of the model in terms of dimer and monomer variable solves the complex action problem. We present results of numerical simulations using a worm algorithm for the specific heat and two-point correlation function of Polyakov loops. Evidences of a first order deconfinement phase transition are discussed. © 2013 American Institute of Physics.
Keywords: Lattice gauge theories; QCD deconfinement phase transition; Worm algorithm